The appropriate surgical procedure according to transperineal ultrasound data in neonates with anorectal malformation - العليان علي; ناصر محـمد; بدور فـواز (Latakia University Journal -Medical Sciences Series, 2022)
Aim of study: Determining the appropriate surgical option based on ultrasound data in measuring the distance between the end of the final colonic sinus and the skin of the perineum, where the supposed anatomical location of the absent anal orifice is located. Methods: During the period between 2016 and 2021 at Tishreen University Hospital and in 2021 at the Children’s and Obstetrics Hospital, a study was conducted on 24 newborns born with Anorectal malformation. Ultrasound imaging was performed for patients to measure after the end of the cecum of the rectum from the skin of the perineum P-P the location of the orifice absent anus. Results : Our study sample was distributed to 7 female patients and 17 males, and the cases were classified according to transperineal ultrasound into 9 cases of the upper type and 15 cases of the lower type, and this was confirmed during the surgical procedure in all cases. Conclusion: Ultrasound imaging can be used to classify Anorectal malformations and thus make the appropriate surgical decision.